The protective effect of Rhizophora apiculata bark extract against testicular damage induced by cigarette smoke in male rats - Syazili Mustofa; Fauziah Hanif (Acta Biochimica Indonesiana, 2019)
Background: The mangrove bark extract (Rhizophora apiculata) is known to have the ability to inhibit the formation of free radicals, act as antioxidants, and anti-inflammatory. Objective: This study was attempted to investigate the potency of Rhizophora apiculata bark extracts as an antioxidant to protect rat testes from the damage due to cigarette smoke exposure. Methods: An experimental study using a posttest-only control group design was employed. Samples consisted of 25 male rats divided into 5 groups, namely K (-) not treated, K (+) exposed to cigarette smoke without the administration of mangrove bark extract, groups P1, P2, and P3 were exposed to cigarette smoke and each group received a dose of Rhizophora apiculata bark extracts every day for 30 days. Furthermore, P1 obtained 28.275 mg/KgBW, P2 was about 56.55 mg/kgBW, and P3 got 113.10 mg/kgBW. Results: Analysis using One Way ANOVA showed that there were significant effects of administration of extracts on the average number of primary spermatocytes and the thickness of the seminiferous tubules in the rats that have been exposed to cigarette smoke when compared to controls. The dose of extract that has the best effect was 113.10 mg/kgBW. Conclusion: Rhizophora apiculata bark extract is indicated to have a protective effect that can prevent damage in rats testes exposed to cigarette smoke.